A honeycomb porous random silicon dioxide and its preparation method and application
By preparing honeycomb -shaped porous and ranging silicon dioxide through aggregation, hydrolysis, and burning process, the problem of complex and cost -high cost of the existing silicon -based pore material preparation process, realized cheap and efficient material preparation, and have good suction inhalation Performance and potential for application of multi -field.
Patent Information
- Application Number
- CN202211428808.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-15
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2042-11-15
AI Technical Summary
The existing silicon-based mesoporous materials with larger pore sizes are prepared under high temperature and high pressure hydrothermal reaction conditions. The reaction time is long, and it is not suitable for mass production, and it is relatively expensive. At the same time, there are few researches on random porous materials, and there is a lack of materials with new characteristics.
The three processes of polymerization, hydrolysis, and burning are used to synthesize the pre -polymer by adding a mixture of copper catalysts in the nitrogen atmosphere, and burning in the air atmosphere to prepare honeycomb -shaped porous random silica.
The efficient utilization of cheap industrial raw materials has been realized, and light -quality, honeycomb -shaped porous inorganic silicon dioxide materials are prepared through simple processes. They have good load metal catalyst capacity and suction performance in the broadband range, and are suitable for a variety of application areas.
Smart Images

Figure CN115924925B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nano material preparation, and relates to a honeycomb porous random silicon dioxide and a preparation method and application thereof. Background Art
[0002] Porous nanomaterials are one of the research hotspots in the field of new materials. They have the characteristics of low relative density, large specific surface area, high porosity, strong selective permeability and permeability, and also have sound absorption and heat insulation effects. Porous materials have many pores, guest molecules can be selectively adsorbed in them, and sometimes chemical transformation can be carried out. They have important application prospects in energy storage, catalysis, supercapacitors, separation adsorbents, desalination, noise reduction, ion exchange, electromagnetic shielding and bone implant biomaterials.
[0003] People use silicon source, water, surfactant, acid or alkali as raw materials, adopt hydrothermal synthesis method and sol-gel method, use different templates and silicon sources, and synthesize a series of silicon-based porous materials with order, novel structure and superior performance, including hexagonal two-dimensional straight channels, cubic three-dimensional cross / cage / cross worm-like channels, layered three-dimensional straight channels, etc., under different synthesis conditions and synthesis methods. The specificity and selectivity of such highly regular silicon-based porous materials have been successfully used to achieve applications in catalysis, separation and adsorption. Despite this, most silicon-based mesoporous materials with larger pore sizes need to be processed under high temperature and high pressure hydrothermal reaction conditions, which takes a long time to react, is not suitable for mass production, and is relatively expensive.
[0004] At present, compared with regular porous materials, the research on random porous materials has received little attention. However, a recent study found that topologically random porous materials have new properties that regular porous materials do not have (Bennett, TD, Coudert, FX., James, SL et al. The changing state of porous materials. Nat. Mater. 2021, 20, 1179–1187.), which has attracted our attention. Summary of the invention
[0005] Based on the shortcomings of the current state of porous silica preparation, the first object of the present invention is to provide a method for preparing honeycomb porous random silica, which starts from cheap industrial raw materials and is easy to realize the industrial production of porous random silica materials through a simple process.
[0006] The preparation process of the honeycomb nano-scale porous random silica described in the present invention comprises three steps: polymerization, hydrolysis and calcination, and adopts the following technical scheme:
[0007] Step (1), under nitrogen atmosphere, add copper catalyst to the mixed solution of N,N,N',N'-tetramethylethylenediamine TMEDA and dimethylsiloxane mixed ring DMC, add acrylate MA and trichlorosilane HSiCl under stirring at room temperature 3 The mixed solution is heated to reflux to obtain a hydrolyzed prepolymer;
[0008] Step (2), adding deionized water to the hydrolyzed prepolymer obtained in step (1) to carry out a hydrolysis reaction, and filtering, washing, drying and grinding to obtain a solid powdery precursor polymer;
[0009] Step (3), calcining the precursor polymer obtained in step (2) in an air atmosphere, and naturally cooling it to room temperature to obtain the honeycomb porous random silica;
[0010] Preferably, the copper catalyst in step (1) is cuprous oxide, cupric oxide, or a mixture of the two. If it is a mixture, the molar ratio of cuprous oxide to cupric oxide is 1:1 to 3.
[0011] Preferably, in step (1), TMEDA, DMC, MA, HSiCl 3 The volume ratio is 0.5~1.5:0.5~1.5:1~3:3~5.
[0012] Preferably, the reaction temperature of step (1) is 50-120° C., and the reaction time is 3-24 h.
[0013] Preferably, the hydrolysis time in step (2) is 0.5 to 8 hours;
[0014] Preferably, the calcination conditions in step (3) are: calcining at 90-100°C for 15 min, then heating to 120-150°C for 15 min, then heating to 170-200°C for 30 min, and finally heating to 450-500°C for 1 h.
[0015] The second object of the present invention is to provide a honeycomb porous random silica prepared by the above method, wherein the pore size is randomly distributed between 100 and 600 nm.
[0016] The third object of the present invention is to provide a silicone rubber / graphene composite material for electromagnetic shielding, comprising the above-mentioned honeycomb porous random silica and a matrix material, wherein the amount of the honeycomb porous random silica is 0.2 vol%.
[0017] Compared with the prior art, the present invention has the following beneficial effects:
[0018] A lightweight, honeycomb-shaped porous inorganic silica material was prepared by a simple process using cheap industrial-grade trichlorosilane, acrylate, and DMC as raw materials. The preparation method has cheap raw materials and simple processes. The irregular honeycomb multi-porous channels formed by the topological structure can not only load metal catalysts well, but also plate a metal layer on the surface of the filler to form multiple interface reflections of electromagnetic waves, which can effectively improve the material's wave absorption performance in a wide frequency range. It has broad prospects in the fields of multiphase catalysis, electromagnetic shielding (wave absorption) materials, adsorption separation, carriers, biomaterials, noise reduction, energy storage, ion exchange, and green chemistry. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 The present invention is a schematic diagram of the process of preparing a honeycomb porous random silica.
[0020] Figure 2 This is a scanning electron microscope image of the porous random silica prepared in Example 2.
[0021] Figure 3 It is the shielding effectiveness of the carbon-based / porous random silica-silicone rubber composite material in Application Example 1 at 2 to 18 GHz.
[0022] Figure 4 This is the microwave absorption performance of the carbon-based / porous random silica-silicone rubber composite material in Application Example 1 at 8 to 12 GHz.
[0023] Figure 5 This is the wave absorption performance of the carbon-based / porous random silica-silicone rubber composite material in Application Example 1 at 12 to 18 GHz.
[0024] Figure 6 This is the 18-26.5 GHz wave absorption performance of the carbon-based / porous random silica-silicone rubber composite material in Application Example 1.
[0025] Figure 7 This is the 26.6-40GHz wave absorption performance of the carbon-based / porous random silica-silicone rubber composite material in Application Example 1. DETAILED DESCRIPTION
[0026] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. The specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0027] The present invention discloses a method for preparing honeycomb porous random silica, and the specific implementation scheme is as follows:
[0028] Step (1), under nitrogen atmosphere, add 0.4-0.5 g of copper catalyst to a mixture of 1-1.5 mL of N,N,N',N'-tetramethylethylenediamine TMEDA and 0-3.1 mL of dimethylsiloxane mixed ring DMC, and add 1-2 mL of acrylate MA and 2-5 mL of trichlorosilane HSiCl under stirring at room temperature; 3 The mixed solution is heated under reflux at 50-150° C. to obtain a hydrolyzed prepolymer;
[0029] The copper catalyst is one of cuprous oxide and cupric oxide or a mixture of the two, and the molar ratio of cuprous oxide to cupric oxide in the mixture is 1:0.25-2;
[0030] The acrylic acid ester includes one or more combinations of methyl acrylate, ethyl acrylate, butyl acrylate, pentyl acrylate and dodecyl acrylate.
[0031] Step (2), adding deionized water to the hydrolyzed prepolymer obtained in step (1) to carry out a hydrolysis reaction for 0.5 to 8 hours, filtering, washing, drying and grinding to obtain a solid powdery precursor polymer;
[0032] Step (3), calcining the precursor polymer obtained in step (2) at 90-100° C. for 15 min in an air atmosphere, heating it to 120-150° C. for 15 min, then heating it to 170-200° C. for 30 min, and finally heating it to 450-500° C. for 1 h, and then naturally cooling it to room temperature to obtain the honeycomb porous random silica.
[0033] The process is as Figure 1 shown.
[0034] The honeycomb porous random silica prepared according to the above scheme has a pore size randomly distributed in the range of 100 to 600 nm.
[0035] Meanwhile, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other. The present invention is further described in detail below in conjunction with the examples, and the raw materials used in the examples can be purchased commercially or prepared by conventional methods.
[0036] Example 1
[0037] 1) Polymerization process: In a 50 mL three-necked round-bottom flask equipped with a condenser and mechanical stirring, 0.5 g of cuprous oxide, 1.5 mL of TMEDA and 3.1 mL of DMC were added under nitrogen protection. After stirring in an ice-water bath for several minutes, 1.8 mL of MA and 4.0 mL of HSiCl were slowly added dropwise. 3The mixed solution was stirred at room temperature for a period of time, and then the temperature of the reaction system was raised to 80° C. and heated under reflux for 5 h. After the reaction raw materials were completely solidified, the reaction was stopped and cooled to room temperature to obtain a hydrolyzed prepolymer.
[0038] 2) Hydrolysis process: add 200 mL of deionized water to the hydrolyzed prepolymer obtained in step 1), continue stirring for 4 h, vacuum filter and wash with water several times until the filtrate is a neutral colorless transparent liquid, vacuum dry at 70° C. for 2 h, and grind to obtain a white powder.
[0039] 3) Calcination process: The white powder obtained in step 2) is placed in a crucible in a muffle furnace, and the calcination temperature is set as follows: 90°C (15min), 150°C (15min), 170°C (30min), 450°C (1h). After cooling to room temperature, the obtained white powder is honeycomb porous silica, and its scanning electron microscope image is as follows Figure 2 shown.
[0040] Example 2
[0041] 1) Polymerization process: In a 50 mL three-necked round-bottom flask equipped with a condenser and mechanical stirring, 0.39 g of cuprous oxide and 0.11 g of cupric oxide, 1.5 mL of TMEDA and 3.1 mL of DMC were added under nitrogen protection. After stirring in an ice-water bath for several minutes, 2.0 mL of butyl acrylate and 2.0 mL of HSiCl were slowly added dropwise. 3 The mixed solution was stirred at room temperature for a period of time, and then the temperature of the reaction system was raised to 50° C. and heated under reflux for 5 h. After the reaction raw materials were completely solidified, the reaction was stopped and cooled to room temperature to obtain a hydrolyzed prepolymer.
[0042] 2) Hydrolysis process: add 200 mL of deionized water to the hydrolyzed prepolymer obtained in step 1), continue stirring for 4 h, vacuum filter and wash with water several times until the filtrate is a neutral colorless transparent liquid, vacuum dry at 70° C. for 2 h, and grind to obtain a white powder.
[0043] 3) Calcination process: The white powder obtained in step 2) is placed in a crucible and placed in a muffle furnace, and the calcination temperature is set as follows: 100°C (15min), 120°C (15min), 200°C (30min), 500°C (1h). After cooling to room temperature, the obtained white powder is honeycomb porous silica.
[0044] Example 3
[0045] 1) Polymerization process: In a 50 mL three-necked round-bottom flask equipped with a condenser and mechanical stirring, 0.39 g of cuprous oxide and 0.11 g of cupric oxide, 1.5 mL of TMEDA and 3.1 mL of DMC were added under nitrogen protection. After stirring in an ice-water bath for several minutes, 1.8 mL of MA and 2.0 mL of HSiCl were slowly added dropwise. 3 The mixed solution was stirred at room temperature for a period of time, and then the temperature of the reaction system was raised to 120° C. and heated under reflux for 5 h. After the reaction raw materials were completely solidified, the reaction was stopped and cooled to room temperature to obtain a hydrolyzed prepolymer.
[0046] 2) Hydrolysis process: add 200 mL of deionized water to the hydrolyzed prepolymer obtained in step 1), continue stirring for 4 h, vacuum filter and wash with water several times until the filtrate is a neutral colorless transparent liquid, vacuum dry at 70° C. for 2 h, and grind to obtain a white powder.
[0047] 3) Calcination process: The white powder obtained in step 2) is placed in a crucible and placed in a muffle furnace, and the calcination temperature is set as follows: 100°C (15min), 130°C (15min), 200°C (30min), 480°C (1h). After cooling to room temperature, the obtained white powder is honeycomb porous silica.
[0048] Example 4
[0049] 1) Polymerization process: In a 50 mL three-necked round-bottom flask equipped with a condenser and mechanical stirring, 0.29 g of cuprous oxide and 0.11 g of cupric oxide, 1.5 mL of TMEDA and 1.5 mL of DMC were added under nitrogen protection. After stirring in an ice-water bath for several minutes, 1.6 mL of dodecyl acrylate and 4.0 mL of HSiCl were slowly added dropwise. 3 The mixed solution was stirred at room temperature for a period of time, and then the temperature of the reaction system was raised to 120° C. and heated under reflux for 5 h. After the reaction raw materials were completely solidified, the reaction was stopped and cooled to room temperature to obtain a hydrolyzed prepolymer.
[0050] 2) Hydrolysis process: add 200 mL of deionized water to the hydrolyzed prepolymer obtained in step 1), continue stirring for 4 h, vacuum filter and wash with water several times until the filtrate is a neutral colorless transparent liquid, vacuum dry at 70° C. for 2 h, and grind to obtain a white powder.
[0051] 3) Calcination process: The white powder obtained in step 2) is placed in a crucible and placed in a muffle furnace, and the calcination temperature is set as follows: 100°C (15min), 130°C (15min), 200°C (30min), 480°C (1h). After cooling to room temperature, the obtained white powder is honeycomb porous silica.
[0052] Application Example 1
[0053] Application of honeycomb porous random silica in silicone rubber / graphene composite materials for electromagnetic shielding: 30g of high-temperature mixed silicone rubber (Dongjue silicone, NE-131), 0.3g of graphene, 0.3g of carbon fiber, 1.5g of nickel-plated graphite (48μm), and 0.20g of dipentadienyl vulcanizer are mixed evenly on an open mill, and pressurized and vulcanized at 175℃ for minutes to prepare 2mm thick and 5mm diameter samples as blank comparison sample specimens. Under the same ratio, adding 0.2vol% of the prepared honeycomb porous silica, the obtained filler can play a good role in enhancing electromagnetic shielding, and can improve the electromagnetic shielding effectiveness of the material in a wide frequency band (2GHz~18GHz) by about 10dB ( Figure 3 ), and is mainly manifested in the absorption performance Figure 4 to Figure 7 .
[0054] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A method for preparing honeycomb porous random silica, characterized in that: The preparation method comprises the following steps: Step (1), under nitrogen atmosphere, adding a copper catalyst to a mixture of N,N,N',N'-tetramethylethylenediamine TMEDA and dimethylsiloxane mixed ring DMC, adding a mixture of acrylate MA and trichlorosilane HSiCl3 under stirring at room temperature, heating and refluxing to obtain a hydrolyzed prepolymer; Step (2), adding deionized water to the hydrolyzed prepolymer obtained in step (1) to carry out a hydrolysis reaction, and filtering, washing, drying and grinding to obtain a solid powdery precursor polymer; Step (3), calcining the precursor polymer obtained in step (2) in an air atmosphere, and then naturally cooling it to room temperature to obtain the honeycomb porous random silica.
2. The method for preparing a honeycomb porous random silica according to claim 1, characterized in that: The copper catalyst described in step (1) is cuprous oxide, cupric oxide, or a mixture of the two, and the molar ratio of cuprous oxide to cupric oxide in the mixture is 1:0.25-2.
3. The method for preparing a honeycomb porous random silica according to claim 1, characterized in that: In step (1), the volume ratio of TMEDA, DMC, MA and HSiCl3 is 1-1.5:0-3.1:1-2:2-5.
4. The method for preparing a honeycomb porous random silica according to claim 1, characterized in that: The reaction temperature of step (1) is 50-150°C.
5. The method for preparing a honeycomb porous random silica according to claim 1, characterized in that: The acrylic acid ester described in step (1) includes one or more combinations of methyl acrylate, ethyl acrylate, butyl acrylate, pentyl acrylate, and dodecyl acrylate.
6. The method for preparing honeycomb porous random silica according to claim 1, characterized in that: The hydrolysis time in step (2) is 0.5 to 8 hours.
7. The method for preparing honeycomb porous random silica according to claim 1, characterized in that: The calcination conditions in step (3) are: calcination at 90-100° C. for 15 min, then heating to 120-150° C. for 15 min, then heating to 170-200° C. for 30 min, and finally heating to 450-500° C. for 1 h.
8. A honeycomb porous random silica, prepared by the method according to any one of claims 1 to 7, characterized in that: The pore size of the honeycomb porous random silica is randomly distributed between 100 and 600 nm.
9. A silicone rubber / graphene composite material for electromagnetic shielding, comprising the honeycomb porous random silica according to claim 8 and a matrix material, characterized in that: The amount of the honeycomb porous random silica used was 0.2 vol%.
Citation Information
Patent Citations
Honeycomb three-dimensional porous silicon / carbon composite material and preparation method thereof
CN105977478A
Honeycomb three-dimensional continuous porous silicon material and preparation method thereof
CN106115708A